Alleviating effect of Lactobacillus rhamnosus SDSP202418 on exercise-induced fatigue in mice - Yang, Yang; Zhao, Yuanji; Lei, Huan (Frontiers in Microbiology, 2024)
In this study, the effects of Lactobacillus rhamnosus SDSP202418 isolated from shrimp paste on the exercise performance of fatigued mice were analyzed, and the potential action mechanism was revealed. L. rhamnosus SDSP202418 significantly improved the exhaustion time of the mice and regulated the biochemical indices (lactate dehydrogenase, nitrogen, and uric acid) of the fatigued mice to resist fatigue. L. rhamnosus SDSP202418 also upregulated the mRNA expression of slow muscle fibers and downregulated the mRNA expression of fast muscle fibers in the exercise mice by activating the AMPK/PGC-1α pathway in the fatigued mice. It also increased the contents of antioxidant enzymes (superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH)) in the liver and muscle. These enzymes removed and repaired oxidative free radicals to achieve antifatigue. In addition, L. rhamnosus SDSP202418 can change the gut microbial structure and modulate the abundance and balance of fatigue-related gut microbiota, which in turn exerts antifatigue effects. L. rhamnosus SDSP202418 is a functional food component that relieves fatigue after exercise.